Frailty in Indigenous Populations: A Scoping Review - Lewis, Ebony T.; Howard, Leanne; Cardona, Magnolia; Radford, Kylie; Withall, Adrienne; Howie, Adam; Rockwood, Kenneth; Peters, Ruth (Frontiers in Public Health, 2021)
Background: Indigenous populations experience high rates of age-related illness when compared to their non-Indigenous counterparts. Frailty is a challenging expression of aging and an important public health priority. The purpose of this review was to map what the existing literature reports around frailty in Indigenous populations and to highlight the current gaps in frailty research within the Indigenous landscape. Method: Scoping review of English language original research articles focusing on frailty within Indigenous adult populations in settler colonial countries (Australia, Canada, New Zealand and USA). Ten electronic databases and eight relevant institutional websites were searched from inception to October 2020. Results: Nine articles met our inclusion criteria, finding this population having a higher prevalence of frailty and frailty occurring at younger ages when compared to their non-Indigenous counterparts, but two did not use a formal frailty tool. Females presented with higher levels of frailty. No culturally specific frailty tool was identified, and the included articles did not assess strategies or interventions to manage or prevent frailty in Indigenous peoples. Conclusions: There was little definitive evidence of the true frailty prevalence, approaches to frailty screening and of potential points of intervention to manage or prevent the onset of frailty. Improvements in the quality of evidence are urgently needed, along with further research to determine the factors contributing to higher rates of frailty within Indigenous populations. Incorporation of Indigenous views of frailty, and instruments and programs that are led and designed by Indigenous communities, are crucial to address this public health priority.